STUDI FENOMENOLOGI PERSEPSI PASIEN DIABETES MELITUS DENGAN KOMPLIKASI DIABETIC FOOT DI RUMAH SAKIT UMUM DAERAH KABUPATEN BULELENG - Gede Budi Widiarta; Putu Agus Ariana; Ayu Clara Kristanto (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2018)
Introduction: Diabetes melitus is commonly known by the name of diabetes that often cause injury of the leg. Diabetic foot are a disorder that occurs in people with diabetes mellitus and become a very potential factor of consequences of a disease such as ulceration, infection, and tissue injury associated with peripheral or metabolic neurological diseorder tah can occur in the lower limbs. Purpose: The purpose of this study to explore the diabetes melitus patient’s perception who have wound on the leg in Rumah Sakit Umum Daerah Buleleng. Methods: The design of this research used qualitative design with phenomenology approach using Colaizzi method. The selection of participant in this research used purposive sampling technique with a number of the participants amount to 7 participants. Results: Collected data use in-depth interviews technique. Analyzed data obtain 4 themes that showed perception of patient with diabetes mellitus who have diabetic foot complications, include: (1) rerationship with others, (2) Negative self – purpose felt during pain, (3) Positive self – response felt during pain, (4) Encouragement to get recovery.